Isolation and Characterization of Alkaline Pectinase Productive Bacillus tropicus from Fruit and Vegetable Waste Dump Soil - Thakur,Pitambri (2021)
Abstract Alkaline pectinase is the utmost significant industrial enzyme of the bioscouring process. By considering bio scouring of cotton, 30 microbial isolates from fruit and vegetable waste rich dump soil of Solang Valley and Vasishta (Manali, Himachal Pradesh, India) were isolated and screened for the alkaline pectinase production in the current research work. Only four isolates P3, P16, P21, and P27 were capable to produce extracellular alkaline pectinase at pH 9. Further by applying submerged fermentation, the alkaline pectinase production was quantitatively screened. The most efficient isolate was P3 identified as Bacillus tropicus, based on morphological, biochemical, and molecular characterization. Molecular characteristics confirmed by 16S rDNA sequence analysis. The nucleotide sequence of the isolate was novel with a 97% similarity index and submitted to the GenBank with accession number MK332379. The Bacillus strain selected was active at broad pH range from 8-10.5 and a temperature range from 25-50 oC. Optimum pH and temperature observed were 9 and 37 oC respectively and can be suitably used for the bio scouring process for the pretreatment of the fabrics.